Bioactive adrenomedullin, proenkephalin A and clinical outcomes in an acute heart failure setting. Issue 2 (3rd July 2019) - Molvin, John; Jujic, Amra; Navarin, Silvia; Melander, Olle; Zoccoli, Giada; Hartmann, Oliver; Bergmann, Andreas; Struck, Joachim; Bachus, Erasmus; Di Somma, Salvatore; Magnusson, Martin
Abstract : Objectives: In an acute heart failure (AHF) setting, proenkephalin A 119–159 (penKid) has emerged as a promising prognostic marker for predicting worsening renal function (WRF), while bioactive adrenomedullin (bio-ADM) has been proposed as a potential marker for congestion. We examined the diagnostic value of bio-ADM in congestion and penKid in WRF and investigated the prognostic value of bio-ADM and penKid regarding mortality, rehospitalisation and length of hospital stay in two separate European AHF cohorts. Methods: Bio-ADM and penKid were measured in 530 subjects hospitalised for AHF in two cohorts: Swedish HeArt and bRain failure inVESTigation trial (HARVEST-Malmö) (n=322, 30.1% female; mean age 75.1+11.1 years; 12 months follow-up) and Italian GREAT Network Rome study (n=208, 54.8% female; mean age 78.5+9.9 years; no follow-up available). Results: PenKid was associated with WRF (area under the curve (AUC) 0.65, p<0.001). In multivariable logistic regression analysis of the pooled cohort, penKid showed an independent association with WRF (adjusted OR (aOR) 1.74, p=0.004). Bio-ADM was associated with peripheral oedema (AUC 0.71, p<0.001), which proved to be independent after adjustment (aOR 2.30, p<0.001). PenKid was predictive of in-hospital mortality (OR 2.24, p<0.001). In HARVEST-Malmö, both penKid and bio-ADM were predictive of 1-year mortality (aOR 1.34, p=0.038 and aOR 1.39, p=0.030). Furthermore, bio-ADM was associated with rehospitalisation (aOR 1.25, p=0.007) and length of hospital stay (β=0.702, p=0.005). Conclusion: In two different European AHF cohorts, bio-ADM and penKid perform as suitable biomarkers for early detection of congestion severity and WRF occurrence, respectively, and are associated with pertinent clinical outcomes.